Knowledge profiling for social networking news releases - Lo, Tse-Yi; Khoo, Vincent Kay Teong (2008)
This paper presents a case study of the news item categorization for a social networking mashup.Since it is time consuming to develop the hierarchical news categories on an iterative and incremental basis using a conventional knowledge mapping approach, an alternative approach is derived by using the Subject Reference System (SRS) guidelines as the reference for categorizing various types of news releases.With the ulterior aim of enabling automatic generation of knowledge maps, this research project adopts only a manual process for the creation of knowledge profile entries, which would then form the input references for future automatic generation of knowledge maps.The approach for transforming a news item to a knowledge profile entry involves some computer-assisted extraction of keywords, which is then linked to the Subject Reference System (SRS) guidelines repository for ease of knowledge profiling.It is argued that the alternative knowledge profiling approach is easier and more efficient than a manufacturing-oriented conventional approach, because the knowledge ontology and validation of news releases have already been proven and accepted by a large community of news agencies